2016
DOI: 10.3390/ijms17122012
|View full text |Cite
|
Sign up to set email alerts
|

Natural Non-Mulberry Silk Nanoparticles for Potential-Controlled Drug Release

Abstract: Natural silk protein nanoparticles are a promising biomaterial for drug delivery due to their pleiotropic properties, including biocompatibility, high bioavailability, and biodegradability. Chinese oak tasar Antheraea pernyi silk fibroin (ApF) nanoparticles are easily obtained using cations as reagents under mild conditions. The mild conditions are potentially advantageous for the encapsulation of sensitive drugs and therapeutic molecules. In the present study, silk fibroin protein nanoparticles are loaded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 66 publications
(83 reference statements)
1
24
0
Order By: Relevance
“…Similarly, Ca 2+ in calcium gluconate also induces the self‐assembly of ApSF nanoparticles . Particles between 200 and 400 nm are obtained by blending aqueous ApSF, Ca 2+ ions, and insulin in a proper mixing ratio.…”
Section: Processing Methodologies and Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Ca 2+ in calcium gluconate also induces the self‐assembly of ApSF nanoparticles . Particles between 200 and 400 nm are obtained by blending aqueous ApSF, Ca 2+ ions, and insulin in a proper mixing ratio.…”
Section: Processing Methodologies and Biomedical Applicationsmentioning
confidence: 99%
“…ApSF NPs are used as a delivery device by different researchers . The RGD sequences in ApSF may specifically target drugs to the cancer cells or angiogenic endothelial cells in tumor stroma by binding cell surface integrin receptors.…”
Section: Processing Methodologies and Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk has been more attracted due to its exceptional qualities like, biocompatibility, superior mechanical properties, and biodegradability. Silk fibroin (SF) is histocompatible, nontoxic, and also optically active, which makes it widely applicable to the biomedical and other fields [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies by Wang et al also showed that positively-charged molecules exhibit a more prolonged or sustained in vitro release of the drugs from the SFNPs compared to negatively charged molecules due to strong electrostatic interactions. 51 The increase of TPL and CL release from SFNPs might also be attributed to the balance of the negative charges inside and outside the silk aggregate. Xiao et al reported that metal ions usually interact with functional groups containing negative charges outside the aggregates while hydrogen ions could neutralize the negative charges both outside and inside the aggregates simultaneously due to their differential capacity of entering into the aggregates.…”
Section: Discussionmentioning
confidence: 99%